Effect of Light on the Photosynthesis, Pigment Content and Stomatal Density of Sun and Shade Leaves of Vernonia Amygdalina - Idris, Aisha; Linatoc, Alona C.; Aliyu, Aisha M.; Muhammad, Surayya M.; Bakar, Mohd Fadzelly Bin Abu (International Journal of Engineering and Technology, 2018)
Light affects the growth and development of plants by influencing the physical appearance of one leaf as well as the appearance of the whole plant. Plant photosynthesis, stomata density, and pigment contents are all influenced by light The objective of this research is to determine the effect of light on the photosynthesis, pigment content and stomatal density of Sun and Shade Leaves of Vernonia amygdalina. Gas exchange was measured using Li-6400 and the data obtained was used to create a light response curve where parameters including light saturation point (LSP), light compensation point (LCP) and apparent quantum yield were estimated. Photosynthetic pigment were quantified spectrophotometrically.Â  Moreover, the stomatal density was counted under light microscope, after making a nail polish impression of the leaf. The results discovered shows that as the light intensity increases, the gas exchange and stomatal density increases while the photosynthetic pigment of the studied plant decreases (P<0.05). In addition, LSP and LCP increases with increasing light intensity. Besides, statistically significant negative correlation (P<0.05) was achieved among stomatal density and transpiration rate thereby leading to a conclusion that sun leaves of Vernonia amygdalina contribute the highest assimilation rate to the plant than shade leaves. Yet, the higher stomatal density of sun leaves provides water saving to the plant.